REGULATION OF THE SYNTHESIS OF NUCLEOTIDE PHOSPHOHYDROLASE AND NEUTRAL DEOXYRIBONUCLEASE: TWO ACTIVITIES PRESENT WITHIN PURIFIED VACCINIA VIRUS - Pogo, Beatriz G. T. (1969)
Regulation of the synthesis of viral nucleotide phosphohydrolase and neutral DNase was investigated by means of DNA and protein inhibitors. These virus-associated activities, previously localized within viral cores, are introduced into host cells with the infecting inoculum. Nucleotide phosphohydrolase was found throughout the cycle of multiplication in a particulate fraction containing viroplasmic matrices. However, the DNase from the inoculum appeared in the supernatant fraction, and the DNase synthesized after infection was associated with the particulate material. The two enzymatic activities belong in the category of “late” functions. It now appears that during morphogenesis of the poxviruses several “late” proteins, some with enzymatic properties, are enclosed within the viral envelopes.